Dying to work : death and injury in the American workplace - Karmel, Jonathan D., 1955- (Ithaca : ILR Press, 2018)
'Dying to Work' is a collection of short stories from and about workers who were injured or killed on the job. The stories are bookended by a brief history of safety laws that still today leave millions of workers without effective compensation and employers without any meaningful incentive to keep their workers safe.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 29, 2018).
Keywords: Industrial accidents -- United States; Industrial safety -- United States; Occupational mortality -- United States; Hazardous occupations -- United States; Industrial hygiene -- United States; Industry; Social services & welfare, criminology; Central / national / federal government policies; Industrial relations, health & safety; Occupational health & safety law, working time law